Characteristics of bivariate biorthogonal wavelet packets - Zhou, Jian-Feng; Liu, Yong (2008 International Conference on Wavelet Analysis and Pattern Recognition, 2008)
Multivariate wavelets are a popular subject in science research. In this paper, the notion of univariate orthogonal wavelet packets is generalized. First, the definition of biorthogonal nonseparable bivariate wavelet packets is given and a procedure for constructing them is presented. Next, the biorthogonality property of biorthogonal bivariate wavelet packets is investigated.